The effects of quickster : A computer reading software on the students' reading speed, reading time and reading comprehension / Mohd. Noor Azman Othman - Othman, Mohd. Noor Azman (Universiti Teknologi MARA Cawangan Pahang, 2000)
The introduction of computer in language learning over the past few years has indeed given tremendous impact on the learning and teaching process per se. Research carried out overseas has shown positive impact on the students who have been exposed to the usage of computer in learning. This study was carried out to look at whether the same noble effect of computer in learning applies in the Malaysian educational setting. The study carried out was aimed at testing the effectiveness of Computer Assisted Language Learning in the UiTM Pahang branch setting. It used a computer reading software to test the effectiveness of reading instructions in helping the students to read better, faster and understand more.